Social Capital in Disaster Management: A Systematic Literature Review of Research Trends from 1998 to 2019 - Isni Wahidiyah Susanto; Bevaola Kusumasari; Anang Dwi Santoso; Oemar Madri Bafadhal (Faculty of Geography, Universitas Gadjah Mada, 2023)
This study investigates how different facets of social capital affect community resilience in The face of disasters. There has not been a thorough study that examines social capital across various types of frequently occurring disasters and across the different phases of a disaster, that is, pre-disaster, during disaster, and post-disaster. Previous research on social capital has been conducted in both developed and developing countries using various disaster cases. To synthesize previous research, identify knowledge gaps, and set the course for future research, this study used a literature review technique. This method is both methodical and rigorous. The current analysis found a rising trend in the amount of research on the use of social capital in disaster management, demonstrating a growing interest in the function of social capital in boosting community resilience in the face of disasters. The findings of this study showed that community resilience in disaster management is influenced by social capital components. The study found that the trust and network components of social capital—which include trust, beliefs, norms, rules, networks, and values—have the greatest effects on community resilience. Greater knowledge of the function of social capital in disaster management and the aspects of social capital that are most important for fostering community resilience are provided by these results, which have a substantial impact on future research and disaster management methods.